2014
DOI: 10.1002/2014gl059824
|View full text |Cite
|
Sign up to set email alerts
|

Decrypting geophysical signals at Stromboli Volcano (Italy): Integration of seismic and Ground‐Based InSAR displacement data

Abstract: We present the integration of seismic and Ground-Based Interferometric Synthetic Aperture Radar system (GBInSAR) displacement data at Stromboli Volcano. Ground deformation in the area of summit vents is positively correlated with both seismic tremor amplitude and cumulative amplitudes of very long period (VLP) signals associated with Strombolian explosions. Changes in VLP amplitudes precede by a few days the variations in ground deformation and seismic tremor. We propose a model where the arrival of fresh, gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The pre-2014 LiDAR-DEM was obtained elaborating the 3D point cloud acquired during an airborne survey carried on May 2012 by "BLOM Compagnia Generale Ripreseaeree S.P.A." (www.blomasa.com). The data were acquired using the Leica ADS80 sensor which has instrumental vertical and horizontal accuracy of ±10/20 cm and ±25 cm, respectively (see [36] for 2012 DEM features). The acquired point cloud has a mean point density of 8 pt/m 2 .…”
Section: Topographic Data and Co-registrationmentioning
confidence: 99%
“…The pre-2014 LiDAR-DEM was obtained elaborating the 3D point cloud acquired during an airborne survey carried on May 2012 by "BLOM Compagnia Generale Ripreseaeree S.P.A." (www.blomasa.com). The data were acquired using the Leica ADS80 sensor which has instrumental vertical and horizontal accuracy of ±10/20 cm and ±25 cm, respectively (see [36] for 2012 DEM features). The acquired point cloud has a mean point density of 8 pt/m 2 .…”
Section: Topographic Data and Co-registrationmentioning
confidence: 99%
“…This temporal delay between the changes in tremor amplitude of the VLP signals and the GBInSAR displacements is interpreted in terms of the different timescales characterizing bulk gas transfer versus slug formation and ascent (Di Traglia et al 2014c). Moreover, discrete Fourier transform analysis of the same displacement time series shows that the most energetic peaks correspond to a period of 256 days, comparable to the residence time in the very shallow magma storage system (10-213 days; Gauthier and Condomines 1999;Gauthier et al 2000).…”
Section: Geological and Volcanological Backgroundmentioning
confidence: 96%
“…Ground deformation analysis by Di Traglia et al (2014c) revealed that changes in the displacement time series extracted in this area are coupled with variations in seismic tremor amplitude and are anticipated by few days by the changes in the amplitude of the very-long-period (VLP) signals. This temporal delay between the changes in tremor amplitude of the VLP signals and the GBInSAR displacements is interpreted in terms of the different timescales characterizing bulk gas transfer versus slug formation and ascent (Di Traglia et al 2014c).…”
Section: Geological and Volcanological Backgroundmentioning
confidence: 98%
See 2 more Smart Citations